Pengembangan Desa Wisata Alam Lubuk Langkap sebagai Peningkat Kesejahteraan Masyarakat di Bengkulu Selatan - Alfiansyah, Alfiansyah; Sahroni, Angrean; Marta, Inuki Yudi; Saputra, Ilham Tirta; Pratama, Reza Agung; Puspitasari, Arum (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research positions tourism as a key driver for rural economic transformation via the Community-Based Ecotourism model. Lubuk Langkap Nature Tourism Village, South Bengkulu, has excellent natural assets (pristine), such as clear rivers and tropical forests, supported by good social capital. However, this potential is structurally constrained by a Severe Institutional Crisis within the Village-Owned Enterprise, marked by informal management, lack of standard accounting, and vulnerability to moral hazard risk (misconduct). The Main Thesis asserts that this institutional crisis is not merely a technical issue but a major root problem that weakens Social Capital, damages community Capability, and risks permanent environmental damage. The study uses in-depth strategic analysis focusing on the New Institutional Economics and an integrated SWOT framework, employing interpretive descriptive qualitative methods. The analysis formulates an integrated Community-Based Ecotourism development strategy within a Governance framework that is Strengthened by Risk a system designed to become more resilient when facing shocks (moral hazard risk). The Integrated Action Strategy includes: (1) Establishing Exclusive Village-Owned Enterprise Regulatory Control Rights over the entrance gate and Environmental Carrying Capacity; (2) Implementing a physical Daily Public Financial Dashboard to prevent misconduct; and (3) Legalizing Village Regulations (Perdes) on Conservation Zoning and Maximum Daily Visitor Limits. Implementing a Niche Premium Operational Business Plan (OBP), detailing a High Pricing Strategy (including a Conservation Fee) and a fair Proportional Revenue Sharing Formula, is key to achieving improved welfare and ecological sustainability in South Bengkulu.